Microstructure and transport properties of cement mortar made with recycled fine ceramic aggregates - Le Li; Ziyi Liu; Wenfeng Liu; Zeyu Wang; Chunsheng Zhou; Qiang Zeng (Developments in the Built Environment)
Effective utilization of recycled ceramics in building materials has received growing interests. This study focuses on the utilization of household ceramic wastes generated by the ceramic manufacturing industry in Jingdezhen. An experimental study on strengths (compression/bending tests), durability indexes (gas permeation/water absorption tests), and microstructure (mercury intrusion porosimetry/scanning electron microscopy techniques) of mortars using fine ceramic aggregate (CA) as a partial and total substitution of natural sand was carried out. Results indicate that (1) CA incorporation improves the compressive/flexural strengths at 20% substitution and further substitution leads to reduction in the strengths; (2) CA-modified mortars possess a higher ressistance against gas permeation and water absorption; (3) CA roughly narrows the critical pore size, and the durability indexes present linear correlations with characteristic pore parameters; (4) reasonable utilization of household ceramic wastes in concrete construction can contribute to waste management along with enhancing concrete properties.